DANUKH NEOLITHIC SITES OF THE MOUNTAINOUS DAGESTAN - Amirhanov, Hizri Amirhanovic; Magomedov, Rabadan Gadzievic; Cecuskova, Dar'a Igorevna (History, Archeology and Ethnography of the Caucasus, 2025)
In the North-Eastern Caucasus, very few Neolithic sites with preserved cultural layers have been identified to date. In this context, the discovery in 2006 of two new sites from this period at the Kharib Pass in the Gumbetovsky District of the Republic of Dagestan was a significant event. These sites were documented by an expedition led by R.G. Magomedov, which conducted archaeological monitoring during road construction work related to the laying of a main gas pipeline. To date, these sites remain at the reconnaissance stage of investigation. At both sites, archaeological materials were collected from areas disturbed by construction activities. At the Danukh 1 site, an additional exploratory trench was made into the slope, revealing the presence of a preserved cultural layer. A distinctive feature of these sites is their location at a high-mountain pass connecting Inner Dagestan with the foothill regions and the Caspian Lowland. This alone raises questions about the potential to examine, based on the materials from these newly discovered sites, the relationship between the Neolithic cultures of the mountainous and lowland parts of the region. Another significant issue requiring further exploration is understanding why these sites are specifically located at a mountain pass, which, from the perspective of natural and geographical conditions, cannot be considered particularly favorable for long-term human habitation. The authors propose that, firstly, during the Neolithic, there was significant penetration of the cultural traditions of the Caspian Plain into the mountains. Secondly, the location of the sites at the pass is explained by the specific hunting practices of the inhabitants of the Danukh sites.